The reading strategies used by male and female colombian university students (2009)
The present paper aimed to discover whether females and males significantly varied in their utilization of reading strategies. The participants were 352 (male=117 female=235) low to intermediate Colombian university students who completed the Survey of Reading Strategies or SORS (Mokhtari and amp; Sheorey, 2002). The results showed that males’ overall strategy use was moderate, as was their use of nearly half of their individual strategies. Females’ overall strategy use was high, as was their use of half of their strategies. Females’ overall strategy use was significantly higher than males’, as was their strategy use on two of the three SORS subscales and on eight strategies. The study provides ideas for teaching strategies and suggests areas for future research. Key words: Reading, gender, reading strategies, reading surveys El objetivo de este trabajo fue descubrir si había diferencias significantes entre el uso de estrategias de lectura entre mujeres y hombres. Los participantes fueron 352 estudiantes (117 hombres y 235 mujeres) de nivel bajo a intermedio, quienes completaron la encuesta de estrategias de lectura (Mokhtari and amp; Sheorey, 2002). Los resultados mostraron que el uso de las estrategias en los hombres fue moderado como también lo fue su uso de casi la mitad de las estrategias individuales. El uso de las estrategias de las mujeres fue significativamente alta en comparación con los hombres, al igual que lo fue el uso de sus estrategias individuales. Las mujeres usaron dos de las tres estrategias de subescala de la encuesta y ocho estrategias. El estudio proporciona ideas para la enseñanza de estrategias y sugiere áreas para investigaciones futuras. Palabras clave: Lectura, género, estrategias de lectura, encuestas de lectura